1997
DOI: 10.1152/ajpgi.1997.273.5.g1061
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin inhibits secretin-induced ductal secretion by interaction with specific receptors on rat cholangiocytes

Abstract: We assessed the effect of gastrin on ductal secretion in normal and bile duct-ligated (BDL) rats. The effect of gastrin on ductal secretion was examined in the presence of proglumide, a specific antagonist for gastrin receptor (GR). We isolated pure cholangiocytes from normal and BDL rats and assessed gastrin effects on secretin receptor (SR) gene expression and intracellular adenosine 3′,5′-cyclic monophosphate (cAMP) levels. We examined the presence of GR mRNA in cholangiocytes by reverse transcription polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
160
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(174 citation statements)
references
References 39 publications
11
160
0
3
Order By: Relevance
“…2,[5][6][7][8][9][10][11] For example, secretin enhances ductal secretory activity by interaction with specific receptors on cholangiocytes, 12 resulting in an increase in intracellular adenosine 3Ј,5Ј-monophosphate (cAMP) levels. [5][6][7]9,13,14 Increased cAMP levels induce the opening of Cl Ϫ channels and activation of the Cl Ϫ /HCO 3 Ϫ exchanger activity, which results in the secretin-induced bicarbonate-rich choleresis in vivo. [5][6][7]10,11,15 We have demonstrated that intrahepatic cholangiocytes are morphologically and functionally heterogeneous.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…2,[5][6][7][8][9][10][11] For example, secretin enhances ductal secretory activity by interaction with specific receptors on cholangiocytes, 12 resulting in an increase in intracellular adenosine 3Ј,5Ј-monophosphate (cAMP) levels. [5][6][7]9,13,14 Increased cAMP levels induce the opening of Cl Ϫ channels and activation of the Cl Ϫ /HCO 3 Ϫ exchanger activity, which results in the secretin-induced bicarbonate-rich choleresis in vivo. [5][6][7]10,11,15 We have demonstrated that intrahepatic cholangiocytes are morphologically and functionally heterogeneous.…”
mentioning
confidence: 99%
“…[5][6][7]9,13,14 Increased cAMP levels induce the opening of Cl Ϫ channels and activation of the Cl Ϫ /HCO 3 Ϫ exchanger activity, which results in the secretin-induced bicarbonate-rich choleresis in vivo. [5][6][7]10,11,15 We have demonstrated that intrahepatic cholangiocytes are morphologically and functionally heterogeneous. 1,8,9,14,16,17 Specifically, we have shown that purified subpopulations of cholangiocytes and intrahepatic bile duct units (IBDU), separated by size, are heterogeneous with respect to secretin receptor (SR) gene expression, secretin-stimulated cAMP synthesis, and secretin-induced anion transport.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The inhibitory effect of gastrin on secretin-stimulated cholangiocyte secretion is mediated via activation of the cholecystokinin-B/gastrin receptors, followed by membrane translocation and activation of the Ca 2+ -dependent PKC and abolishment of secretin-stimulated cAMP synthesis (103,109). Gastrin also induces membrane translocation of PKC in Mz-ChA-1 cells (134).…”
Section: Inhibition Of Basal and Secretin-stimulated Cholangiocyte Sementioning
confidence: 99%